Solar-powered adsorption-based atmospheric water harvesting systems: Principles, materials, performance analysis, and configurations. (December 2022) - Sadek, S.; Deng, Shuai; Zhao, Jie; Zayed, Mohamed E.
Abstract: The extraction of water from the air is considered one of the promising methods to supply fresh water, especially in arid regions. Recently, the adsorption-based atmospheric water harvesting (AWH) systems are one of the most efficient solutions for water extraction from the atmosphere due to their ability to work under low relative humidity conditions using solar energy or other low-grade energy sources. The current work presents a literature review of the adsorption-based AWH systems from perspectives of adsorbent materials, performance analysis, energy requirements, and system configurations. The adsorption behaviour and selection criteria of the recent promising adsorbents, especially metal–organic frameworks (MOFs), are discussed as well. Moreover, a generalized performance analysis is presented to discuss and analyze the performance parameters and energy requirements for the adsorption-based AWH systems. Finally, a critical discussion of the adsorption-based AWH systems is conducted, and recommendations for future works are highlighted to increase water productivity and enhance the system's performance. The reviewed results highlighted that the adsorption-based AWH systems have achieved water productivities of (0.10–2.80 l/kg) under different conditions. Subsequently, it can be inferred that the obtainable freshwater production is still inadequate to supply water demand with an insufficiency of the long-term stability and real practical utilization of large-scale AWH systems. It is also indicated that the Cr-soc-MOF-1, (Cr) MIL-101, Co2 Cl2 (BTDD), and (Cr) MIL-101(NH2 ) are recommended to be used as adsorbents in future studies of solar adsorption-based AWH systems. It can be recommended that more studies should be carried out considering the recommended suggestions for adsorbent materials and system design to overcome the challenges and for further improvements to make these types of devices more efficient and competitive with other kinds of desalination systems.